Hybrid spline collocation method for transient heat transfer in genrating fin. - Amri Ramli, Ahmad Lutfi (Universiti Sains Malaysia, 2016)
In this reaserch. we developed a new method called Hybrid Spline for solving Partial Differential Equations. We studied the transient response of fins is of vital interest in studying the performance of heat sinks for electronics high speed aircraft, intermittently operating heat exchangers. control equipment. electric motors clutches, and solar systems. Using the above method the approximated solution of proposed problems is computational economical and time saving due the low degree and fast computational of derivatives.